Multiple impact response of temperature-dependent carbon nanotube-reinforced composite (CNTRC) plates with general boundary conditions. (15th March 2017) - Zarei, Hamed; Fallah, Mohadeseh; Bisadi, Hosein; Daneshmehr, AliReza; Minak, Giangiacomo
Abstract: In the present paper, the impact response of CNTRC plate with arbitrary boundary conditions subjected to the simultaneous multiple masses in thermal environments is investigated. It is assumed that the CNT reinforcement is graded along the plate thickness either uniformly or functionally. The extended rule of mixture is applied to estimate the effective material properties of reinforced composite plate and temperature dependent properties are taken into consideration. The governing equations are derived based on the high-order shear deformation theory using Hamilton's principle and the contact behavior between the impactor and the plate is treated by Hertzian nonlinear contact law. A Ritz based approach in conjunction with the fourth order Runge-Kutta technique is employed to solve the governing equations. The verification of the present model is accomplished by comparing its results by those published in the literature and good agreement is achieved. A comprehensive sensitivity analysis is conducted to study the effect of various involved parameters such as CNT volume fraction and its profile distribution along the thickness, boundary conditions, temperature rising and in-plane loading on time histories of the contact force, indentation and lateral deflection at both impact position and the center of plate.